Termination in Psychoanalytic Psychotherapy: An Attachment Perspective - Jeremy Holmes (EJP import test, 2014)
Summary: Attachment and separation are inseparable. To become attached is to suffer the possibility of loss. In this brief, rather discursive, and personal paper I consider different patterns and styles of termination in relation to the characteristic ways in which the secure and insecurely attached make, and therefore break their relationships, and how understanding those patterns can be put to therapeutic use. The avoidantly insecure deny the affective aspects of stopping therapy, and need to be helped to see how anger, fear and sadness are denied but still influence their behaviour; the ambivalently attached cling to therapy and have to be prized away, building a sense of autonomy and confidence that, via ‘reinstatement of the lost object’, they can survive termination secure in the comfort of an inner therapist to turn to at times of need. For the disorganisedly attached, termination is a major threat, and attenuated endings are probably the best arrangement. These themes are discussed with clinical, personal and cinematic examples.
Keywords: attachment; Loss; Psychoanalysis; Separation; Termination